In Situ Synthesis Mechanism and Photocatalytic Performance of Cyano-Bridged Cu (I)/Cu (II) Ultrathin Nanosheets - Li, Shixiong; Qiang, Jiawei; Lu, Lifei; Yang, Shaolong; Chen, Yufeng; Liao, Beiling (Frontiers in Chemistry, 2022)
In-situ synthesis of cyano-bridged Cu(I)/Cu(II) complexes usually requires organometallic catalysts or is carried out under high temperature and high pressure conditions. Herein, the cyano-bridged two-dimensional Cu(I)/Cu(II) photocatalyst: [Cu2(Py)3(CN)3]n (1), is synthesized in-situ at room temperature. The in-situ synthesis mechanism of 1 shows that the partial Cu(II) complex catalyzed the C-C bond cleavage of 1,3-isophthalonitrile (L) to introduce -CN and generate Cu(I)/Cu(II). Its ultrathin nanosheets can be obtained by adding sodium dodecyl benzene sulfonate and performing ultrasonic synthesis in the process of synthesis 1. The ultrathin nanosheets of 1 have a lattice distance of about 0.31 nm and it can rapidly decompose methylene blue (MB) (K = 0.25 mg·L-1·min-1 at pH=3). This research work is beneficial for in-situ synthesis of cyano-bridged Cu(I)/Cu(II) complexes at room temperature, and explore their synthesis and photocatalytic mechanism.